1996
DOI: 10.1051/jp4:19968156
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency Internal Friction Induced by Structural Relaxation of Metallic Glasses

Abstract: A quantitative model of visco-plastic damping induced by structural relaxation of metallic glasses is developed. The model is shown to be consistent with the experiment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…However, their experiments have been performed at high frequency, typically a few kilohertz or even more (a few megahertz) in the case of ultrasonic investigation [30,[32][33][34][35]40,41]. Since ␣ relaxation is shifted towards higher temperature when the testing frequency is increased, this relaxation may be hindered by the onset of crystallization.…”
Section: Influence Of Testing Frequency During a Continuous Heatingmentioning
confidence: 96%
See 1 more Smart Citation
“…However, their experiments have been performed at high frequency, typically a few kilohertz or even more (a few megahertz) in the case of ultrasonic investigation [30,[32][33][34][35]40,41]. Since ␣ relaxation is shifted towards higher temperature when the testing frequency is increased, this relaxation may be hindered by the onset of crystallization.…”
Section: Influence Of Testing Frequency During a Continuous Heatingmentioning
confidence: 96%
“…In oxide glasses, the ␣ relaxation is also observed, but the ␤ relaxation is not systematically present and, when it occurs, it can be due to the presence of water or local movements of foreign ions. In bulk metallic glasses, different investigations have been reported [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. However, a lot of questions are still open, for instance: (i) what is the influence of structural relaxation and crystalliza- tion on the complex modulus?…”
Section: Introductionmentioning
confidence: 99%
“…However, many questions have not been addressed: (i) What is the influence of temperature of the mechanical properties of cerium-based BMG above the room temperature? (ii) It is well known that in amorphous materials, in addition to elasticity and plasticity, a viscoelastic component exists, with a magnitude which may be very large in the supercooled liquid region [11][12][13][14][15][16][17][18][19][20][21]. What's about cerium-based materials?…”
Section: Introductionmentioning
confidence: 98%
“…An estimation [29] has shown that this viscoplastic mechanism is dominating in as-cast MG at frequencies o 1 10 s-l. Obviously, at higher o the anelastic component caused by reversible transitions in two-level relaxation centres will increase. Therefore, an analysis of damping mechanisms at various frequencies promises new valuable information about reversible and irreversible relaxations and their relationship in as-cast and annealed states.…”
Section: Internal Friction Under Intensive Structural Relaxationmentioning
confidence: 99%
“…The first quantitative model of viscoplastic IF due to structural relaxation (the mechanism B) was developed in [29,41] and an expression for Q& was derived:…”
Section: Internal Friction Under Intensive Structural Relaxationmentioning
confidence: 99%